Contemplative pedagogies for transformative teaching, learning, and being - Lin, Jing, 1962-; Culham, Tom E.; Edwards, Sachi (Transforming education for the future., 2019)
"In our current systems of education, there is a trend toward compartmentalizing knowledge, standardizing assessments of learning, and focusing primarily on quantifiable and positivist forms of inquiry. Contemplative inquiry, on the other hand, takes us on a transformative pathway toward wisdom, morality, integrity, equanimity, and joy (Zajonc, 2009). These holistic learning practices are needed as a counterbalance to the over-emphasis on positivism that we see today. In addition to learning quantifiable information, we also need to learn to be calmer, wiser, kinder, and happier. This book aims to find and share various pathways leading to these ends. This book will describe educational endeavors in various settings that use contemplative pedagogies to enable students to achieve deep learning, peace, tranquility, equanimity, and wisdom to gain new understanding about self and life, and to grow holistically. Embodiment is a central concept in this book. We hope to highlight strategies for exploring internal wisdoms through engaging ourselves beyond simply the rational mind. Contemplative pedagogies such as meditation, yoga, tai chi, dance, arts, poetry, reflective writing and movements, can help students embody what they learn by integrating their body, heart, mind, and spirit"--